P626Deletion of toll-like receptor 9 aggravates diastolic heart failure induced by serca2a ablation. (15th July 2014) - Holmen, YD; Sjaastad, I; Yndestad, A; Finsen, AV; Ranheim, T; Alfsnes, K; Gullestad, L; Aukrust, P; Christensen, G; Vinge, LE
Abstract: Purpose: Immune activation plays a nodal role in the pathogenesis of heart failure (HF) and Toll-like receptor 9 (TLR9) signaling significantly impacts the development of systolic HF. However, the consequence of altered TLR9 activity in diastolic HF is unknown. Methods: We engaged in a 3-generation breeding strategy using αMHC-MerCreMer Serca2a flox/flox mice crossed with TLR9-/- mice to generate several comparable mouse lines. Employing these various genetic mouse lines we addressed the importance of TLR9 on progression of diastolic HF, the latter by temporally restricted depletion of cardiac myocyte SERCA2a. Mice were allocated to two substudies; 1) a 12 week survival study registering spontaneous death or signs of severe morbidity according to pre-specified criteria (leading to euthanasia) and 2) a study examining mice at baseline, 3 weeks and 6 weeks by MRI and echocardiography. After imaging at 6 weeks mice were euthanized and tissue and blood were harvested. Results: All mice depleted of cardiomyocyte SERCA2a, but none with the SERCA2a gene intact, reached our pre-specified end-parameter within 73 days. The presence of TLR9 in this model of diastolic HF led to significant improvement in survival with a median life expectancy of 62.5 days as compared to 58 days when the TLR9 gene was deleted (p=0.007). In accordance with these findings serial imaging demonstrated an earlier onset of left ventricular restrictive filling abnormalities in the HF group depleted of TLR9. Significantly larger left atria, lower end-systolic and end-diastolic left ventricular volumes and lower stroke volumes could be detected. Conclusions: The presence of TLR9 augments the development of diastolic HF induced by SERCA2a depletion. This observation may pave the road for novel diastolic HF treatment strategies.